ANALISIS PEMASARAN; BERSAING DI PASAR GLOBAL - Pratama, Mochammad Nova Rizqi Ade; Manafe, Leonard Adrie; Lestari, Sri (JIMEK : Jurnal Ilmiah Mahasiswa Ekonomi, 2023)
Companies in running their own business are certainly inseparable from how the strategy is implemented so that they are able to sell their products globally and thoroughly. Marketing strategy is important and influential for businesses and companies. The purpose of this study was conducted to analyze the marketing of raffia rope products in competing in the global market at UD. Jaya Abadi (JA). The research was conducted using qualitative methods by means of literature studies and interviews with five informants. The results of the research show that JA in competing in the global market implements Segmentation, Targeting, Positioning strategies, and distributes locally and internationally. The data shows that raffia rope products have adequate strength and are resistant to physical damage. In addition, raffia rope can also be recycled and has lower carbon content compared to conventional packaging materials. This study also considers the economic aspect, by analyzing the production costs and potential benefits associated with the use of raffia rope. The use of raffia rope as a packaging material can be a sustainable and environmentally friendly alternative. Taking into account the environmental and economic benefits, the use of raffia contributes to reducing the negative impact of the packaging industry on the environment. Further studies can be conducted to explore the practical application and global market potential of raffia as a sustainable packaging material.